Pengaruh Spiritualitas Produk Dan Spiritualitas Promosi Pada Keputusan Pembelian Online Yang Dimediasi Oleh Loyalitas Pelanggan - Ivang Arielya Deva Mahendra; Wafiatun Mukharomah (Universitas Muhammadiyah Surakarta, 2023)
This study aims to analyze the effect of spirituality products and spirituality promotion on online purchasing decisions which are dissipated by loyalty. This research is a type of quantitative research. The population and sample of this research are the public who make online purchases as many as 85 people. Sources of data used in this study is primary data. Methods of data collection using a questionnaire. Data analysis using SmartPLS software. The results of this study indicate that product spirituality has a significant effect on loyalty, promotion of spirituality has a significant effect on loyalty, while product spirituality has no effect on purchasing decisions. In addition, the promotion of spirituality has an effect on purchasing decisions, then for loyalty has a significant effect on purchasing decisions, and for loyalty mediates positively between the influence of spirituality products on purchasing decisions and loyalty is also able to mediate the influence of spirituality promotion on purchasing decisions.